IDENTITY EDUCATION - Juszczyk-Rygallo, Joanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Family was the basis of socialization in traditional society. Older generation transmitted values to younger generation. Individuals accepted the social roles defined in the society. Nowadays, the socio-cultural conditions changed, which released individuals from the social destiny, but also shook their belief in traditional values. Now, children try to eliminate this loss of sense of identity through interactions with surroundings. However, they always look for more attractive development environment, therefore their interactions concern rather the virtual world than the real one. All personal relationships are weakened in virtual society. The influence of primary environments (family, neighborhood, peers) is marginalized. Thus, it is more and more difficult to achieve relatively stable points of reference – role models – which enable children to find who they want to be. Currently children search them beyond primary social structures, mostly within the scope of virtual communities. Thus, the most important role model for a child is the Internet with its resources, which sometimes does not support normal development. Therefore, defining oneself by the child is more reflexive and subjective. Hence, socialization of children becomes individual, personal and unique. Consequently, there is a need to establish a new space for socialization – the process of identity education. This article is an analytical description of the complex socialization of a child in the contemporary world. Against this background, it attempts to characterize conditions necessary to base this process on identity education as an act of self‑knowledge.